Dynamics of Forming Multicultural Awareness of Students at SMKN 5 Gorontalo - Bunta, Abd. Firman; Sarina, Sarina; Wicaksono, Muhammad Arif; Dotutinggi, Sanri J. (Universitas Pahlawan Tuanku Tambusai, 2026)
Multicultural education has a strategic role in forming inclusive attitudes and harmonious social relations in a pluralistic school environment. However, the study of multicultural education has tended to emphasize curricular and cognitive approaches, thus ignoring the role of school social and cultural practices in shaping students' multicultural awareness. This study aims to analyze how school culture shapes students' multicultural awareness and identify challenges in the process of its formation at SMK Negeri 5 Gorontalo. The research uses a qualitative method with a descriptive approach through observation, interviews, and documentation. The results of the study show that students' multicultural awareness is more predominantly formed through daily social practices based on local wisdom, such as collective work, deliberation, and cross-cultural interaction. However, this awareness is still implicit and faces challenges in the form of a lack of reflection on values, exclusive social relations, and a reduction in multicultural meanings in symbolic practices. This study concludes that strengthening school culture needs to be directed at the development of reflective mechanisms so that students' multicultural awareness develops critically and sustainably